Upaya Meningkatkan Kemampuan Passing Kaki Bagian Dalam Pada Permainan Sepak Bola Dengan Metode Demonstrasi - Triyanto, Sugeng; Daryanto, Zusyah Porja (Journal Sport Academy, 2022)
The problem in this research is "How to improve the ability to pass the inner leg in soccer games with the demonstration method for fifth grade students at SD Negeri 04 Teluk Kebau, Sekadau Regency?". The purpose of this study was to improve the ability to pass the inner leg in soccer games with the demonstration method for fifth grade students at SD Negeri 04 Teluk Kebau, Sekadau Regency. The problem variable in this research is the passing of the inner leg, and the action variable in this research is the Demonstration Method. demonstration to fifth grade students at SD Negeri 04 Teluk Kebau, Sekadau Regency. The subjects in this study were 15 students of class V, totaling 15 students. From the data analysis, it was found that: (1). The application of the demonstration method in the learning process of the ability to pass the inner leg in a soccer game with the demonstration method in class V SD Negeri 04 Teluk Kebau, Sekadau Regency. This can be seen from the increase in learning to pass the inner leg from the pre-cycle of 26.667% then the first cycle of 53.333% and the second cycle of 86.667%. (2). The positive response experienced a significant increase. This is illustrated by the increase in the value of the student's inner leg passing test from cycle I to cycle II. (3). There is an increase in learning to pass the inner leg using the demonstration method for fifth grade students at SD Negeri 04 Teluk Kebau, Sekadau Regency